Computer aided design algorithms for polyvalent gripper systems - Gorce, P.; Villard, C.; Fontaine, J.G.; Bidaud, P. (IEEE International Conference on Systems, Man and Cybernetics, 1993, 1993)
In this paper we present a methodological approach to design polyvalent gripper systems (PGS). It is composed by a set of algorithms which allow to tackle and to solve key steps of design: grasp force planning, grasp mechanism (rigid or manipulable) designing, kinematic chain designing (to realize "configuration" mobilities). To do this, we used some heuristics in order to obtain an optimal solution for each design problems. In the following stages, we will give more details on these polyvalent systems and we develop these algorithms. To illustrate the results obtained by this approach, we will give an example of PGS designing.< >